Post-transplantation cyclophosphamide for graft-versus- host disease prophylaxis in multiple myeloma patients who underwent allogeneic hematopoietic cell transplantation: first comparison by Donor Type. A study from the chronic malignancies working party of the European Society for Blood and Marrow Transplantation - Sahebi, Firoozeh; Eikema, Dirk-Jan; Koster, Linda; Kroger, Nicolaus; Meijer, Ellen; van Doesum, Jaap A.; Rovira, Montserrat; Koc, Yener; Angelucci, Emanuele; Blaise, Didier; Sammassimo, Simona; McDonald, Andrew; et al. (Transplantation and cellular therapy, 2021)
Graft-versus-host disease (GVHD) remains among the major causes of treatment failure in patients with multiple myeloma (MM) undergoing allogeneic hematopoietic cell transplantation (allo-HCT). The use of post-transplantation cyclophosphamide (PT-Cy) is now a well-established and widely used method for GVHD prophylaxis after HLA haploidentical HCT. However, the rationale for using PT-Cy in the setting of matched donor transplantation is less apparent, given the lesser degree of bidirectional alloreactivity. In this retrospective study, we investigated the role of PT-Cy as GVHD prophylaxis in patients with multiple myeloma underoing allo-HCT, among different donor types, to determine cumulative incidence of acute and chronic GVHD and impact on engraftment, progression-free survival (PFS), GVHD-free/relapse- free survival (GRFS), overall survival (OS), and NRM A total of 295 patients with MM underwent allo-HCT using grafts from a matched related donor (MRD; n = 67), matched unrelated donor (MUD; n = 72), mismatched related or unrelated donor (MMRD/MMUD, 1 antigen; n = 27), or haploidentical donor (haplo; n = 129) using PT-Cy between 2012 and 2018. In addition to PT-Cy, agents used in GVHD prophylaxis included calcineurin inhibitors in 239 patients (81%), with mycophenolate mofetil in 184 of those 239 (77%). For grade II-IV acute GVHD, the cumulative incidence at day +100 was 30% (95% confidence interval [CI], 25% to 36%), 9% (95% CI, 5% to 12%) for grade III-IV acute GVHD, and 27% (95% CI, 21% to 32%) for chronic GVHD (limited, 21%; extensive, 6%), with no differences by donor type. The median time to neutrophil engraftment was 19d (95% CI, 18-19), with no significant difference by donor type. The median time to platelet engraftment was delayed in haploidentical donor graft recipients (27 days versus 21 days; P < .001). Two-year OS, PFS, GRFS, and NRM were 51% (95% CI, 45% to 58%), 26% (95% CI, 20% to 32%), 24% (95% CI, 18% to 30%), and 19% (95% CI, 14% to 24%), respectively, with no significant difference between different donor types. In multivariable analyses, compared with the haplo donors, the use of MRDs was associated with significantly better OS (hazard ratio [HR], 0.6; 95% CI, 0.38 to 0.95; P = .029), and the use of MUDs was associated with a significantly higher GRFS (HR, 0.63; 95% CI, 0.42 to 0.97; P = .034). There was a trend toward improved PFS with use of MUDs (HR, 0.69; 95% CI, 0.46 to 1.04; P = .08). Our data show that PT-Cy in MM patients undergoing allo-HCT resulted in low rates of acute and chronic GVHD and led to favorable survival, especially in the matched related donor setting. © 2021 American Society for Transplantation and Cellular Therapy. Published by Elsevier Inc.